PERKEMBANGAN ARSITEKTUR MASJID: SUATU TRANSFORMASI BENTUK DAN RUANG - Barliana, M. Syaom (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2008)
Mosque, is a living culture, because it is an architectural product which is always created, extensively used by Muslim society, utilized continuously from generation to generation. As a religious building, mosque represents Muslim community who constructs and makes it prosperous in terms of extensive use of it for religious and social activities. As a product of prevailing culture, mosque often grows and dynamically develops along with the growth and development of the society itself. The following study is to show the dynamic of development and change in mosque architectural design in Indonesia, by bringing to light the traditional and modern form of transformation and architectural space as its dominant character.